1989
DOI: 10.1056/nejm198901193200302
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Expression of Dystrophin in Symptomatic Carriers of Duchenne's Muscular Dystrophy

Abstract: A deficiency of the protein dystrophin is known to be the cause of Duchenne's muscular dystrophy. To examine the expression of dystrophin in symptomatic female carriers of this X-linked recessive disorder, we performed immunohistochemical studies on muscle-biopsy specimens from three such carriers, using an antiserum raised against a synthetic peptide fragment of dystrophin. In all three carriers, most individual muscle fibers reacted either strongly or not at all to the antiserum for dystrophin; only 2 to 8 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(38 citation statements)
references
References 17 publications
2
34
0
2
Order By: Relevance
“…18) Dystrophin labeling of muscle biopsies from manifesting carriers shows a mosaic pattern, with reduced or absent dystrophin. 33,34) Immunohistochemistry findings are concordant with western blot analysis for dystrophin. 34) No association is seen between the pattern of distribution of dystrophin and clinical severity of manifesting carriers.…”
Section: Insights Of Diagnostic Strategies Of Female Carrier Of Dmd: supporting
confidence: 56%
“…18) Dystrophin labeling of muscle biopsies from manifesting carriers shows a mosaic pattern, with reduced or absent dystrophin. 33,34) Immunohistochemistry findings are concordant with western blot analysis for dystrophin. 34) No association is seen between the pattern of distribution of dystrophin and clinical severity of manifesting carriers.…”
Section: Insights Of Diagnostic Strategies Of Female Carrier Of Dmd: supporting
confidence: 56%
“…2,5). These include analysis of protein polymorphisms to distinguish Xa and Xi expression (6), detection of mosaic expression of a protein in tissues of heterozygous carriers of X-linked disorders (7)(8)(9), or comparison of protein or transcript levels among individuals with different numbers of X chromosomes (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Immunofluorescence studies of dystrophin localization in Becker dystrophy patients have found a disease-specific "patchy" immunofluorescent pattern (7,8). Though (12,13).…”
mentioning
confidence: 99%
“…Becker Moreover, dystrophin deficiency has been shown to be specific for Duchenne muscular dystrophy by both techniques (10,12) (Figs. 1 and 5).…”
mentioning
confidence: 99%